2009
DOI: 10.1097/pep.0b013e3181beb039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aquatic Aerobic Exercise for a Child with Cerebral Palsy: Single-Subject Design

Abstract: These findings suggest that an aquatic aerobic exercise program was effective for this child with cerebral palsy and support the need for additional research in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
19

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 36 publications
0
46
0
19
Order By: Relevance
“…Hydrotherapy program leads to growth at all levels of ICF and increases children's motivation levels (level III evidence) [6]. It was also found to have a positive effect on physical performance and vital capacity and range of motion (level I evidence) [1].…”
Section: Body Function and Structurementioning
confidence: 98%
See 3 more Smart Citations
“…Hydrotherapy program leads to growth at all levels of ICF and increases children's motivation levels (level III evidence) [6]. It was also found to have a positive effect on physical performance and vital capacity and range of motion (level I evidence) [1].…”
Section: Body Function and Structurementioning
confidence: 98%
“…The effect of hydrotherapy on the participation of spastic cerebral palsy children was confirmed in only two papers-(Level I evidence) [3], (level III evidence) [6] and it was further remarked that there is need for further research in this area (level A evidence) [5,8,18] (Figure 1). …”
Section: Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have concluded that performing motor skills in the water can potentially increase confidence and lead to less resistance to difficult tasks compared with land training [10]. Moreover, activities in water can be fun and considered a new experience for children, that result in enhancing motivation and interest [11].…”
mentioning
confidence: 99%